2020
DOI: 10.1016/s2213-8587(20)30300-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of canagliflozin on anaemia in patients with type 2 diabetes and chronic kidney disease: a post-hoc analysis from the CREDENCE trial

Abstract: Effects of canagliflozin on anaemia in patients with type 2 diabetes and chronic kidney disease: a post-hoc analysis of the randomised, double-blind, multicentre CREDENCE trial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 31 publications
4
78
1
6
Order By: Relevance
“…In the DKD groups, we deciphered active glomerulotubular cell-to-cell interactions. In a tubule-centric view (29), the upregulation of SGLT1 and SGLT2 in PCT induced the alteration of glomerulotubular communication and hyperfiltration, explaining the renoprotective mechanisms of the novel agent SGLT2 inhibitor in DKD treatment (30)(31)(32). Nevertheless, the levels of SGLT1 and SGLT2 were not significantly altered in PCT in this study.…”
Section: Discussionmentioning
confidence: 50%
“…In the DKD groups, we deciphered active glomerulotubular cell-to-cell interactions. In a tubule-centric view (29), the upregulation of SGLT1 and SGLT2 in PCT induced the alteration of glomerulotubular communication and hyperfiltration, explaining the renoprotective mechanisms of the novel agent SGLT2 inhibitor in DKD treatment (30)(31)(32). Nevertheless, the levels of SGLT1 and SGLT2 were not significantly altered in PCT in this study.…”
Section: Discussionmentioning
confidence: 50%
“…This study demonstrated that the use of SGLT2i was associated with higher hemoglobin among diabetics with advanced CKD. Although multiple previous clinical trials have shown that the use of SGLT2i increases hemoglobin levels (7)(8)(9)(10)(11), most of these studies excluded patients with eGFR <30mL/min/1.73m 2 . One study on CKD stage 3,4 (15) included only 12 patients with eGFR <30 mL/min/1.73m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…SGLT2i were also reported to increase hemoglobin levels in multiple clinical trials (7)(8)(9)(10)(11). Bene cial effects of SGLT2i on cardiovascular events seem to be at least partially mediated by improvement in anemia (12).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These effects on erythropoiesis suggest that SGLT2 inhibitors may reduce the incidence of anemia. The post-hoc analysis of the CREDENCE trial by Megumi Oshima et al found that the risk of anemia or the risk of starting anemia treatment in the anemia group of patients with type 2 diabetes and chronic kidney disease was significantly lower than that of the placebo group (Oshima et al, 2020). In the exploratory analysis of EMPA-REG test data, the increase in hematocrit during empagliflozin treatment was closely related to beneficial cardiovascular outcomes (Inzucchi et al, 2018).…”
Section: Mechanismsmentioning
confidence: 99%